Spatio-temporal pattern of short birth interval and associated factors on women in Ethiopia: Using Ethiopian demographic and health surveys 2000–2016 - Arega, Gezachew G.; Mitku, Aweke A.; Fenta, Haile M. (Frontiers in Medicine, 2023)
Background: A short birth interval is a critical factor that contributes to a large number of maternal and infant mortality in low- and middle-income countries. It is the major cause of maternal and child mortality in Ethiopia. This study aimed to explore the spatiotemporal distribution of short birth interval in Ethiopia using data from four (2000, 2005, 2011 and 2016) consecutive demographic and health surveys. Methods: A total of 34930 women were included in four consecutive Ethiopian Demographic and Health Surveys. Thus, spatial autocorrelation, hotspot analysis, cluster analysis, and spatial interpolation were carried out for each survey separately to show the temporal pattern of geographically risk areas of short birth intervals in Ethiopia. Finally, the highest proportion of (SBI)short birth interval risk areas in each survey period was mapped. Geospatial analysis was conducted by using ArcGIS V.10.8 and R version 4.2. Results: The results of the study indicated that the overall proportion of short birth intervals of women in Ethiopia was highest in 2000(47.5%), 2005(46.4%), 2011(44.7%), and the lowest in 2016 (44.0%). The values for Global Moran’s I (MI=0.177665 p=0.0016, MI=0.2024, p=0.001, MI=0.10023, p=0.002, and MI= 0.764, p=0.008) showed that the presence of significant short birth interval clustering in Ethiopian administrative zones in 2000, 2005, 2011, and 2016 respectively. The Hotspot areas of short birth interval were consistently observed in the zones of Somali and zones of Hareri Regions in all EDHS years. In addition, the survival status of the index child, residence, breastfeeding practice, religion, and the spatial variable (Si) were significantly associated with the short birth interval of women in all EDHS years. Conclusions: Spatial distribution of short birth intervals differs across Ethiopian administrative zones. Survival status of the index child being dead, rural residential, and no breastfeeding practice as the risk factors for short birth intervals of women that increases the risk of short birth interval among women in all EDHS years. Therefore, the hotspot areas and indicators need interventions to decrease the short birth interval of women.